Pemantauan Router CPE pada Jaringan Metro Ethernet Menggunakan Zabbix Berbasis Raspberry Pi - Hartono, Aris; Oktiawati, Unan Yusmaniar (Journal of Internet and Software Engineering, 2021)
The development of information and communication technology, especially in this digital era, demands communication takes place quickly and the management of network connectivity efficiently and effectively. In line with this, PT Indonesia Comnets Plus have built the Metro Ethernet network which is an ethernet network technology implemented in a metropolitan area (big cities). The company provides an internet network due to providing the best quality network is compulsory. Hence, we need a Metro Ethernet network monitoring system with the aim of being able to know the performance and problems efficiently and in real time. One of the open source based applications used for network monitoring is Zabbix. This study aims to create and test the performance of Raspberry Pi in the Metro Ethernet network monitoring system at PT Indonesia Comnets Plus with the case study of DISKOMINFO in Garut Regency using the Zabbix application. In monitoring, the SNMP (Simple Network Monitoring Protocol) protocol is needed which will send network problems in the form of triggers. Trigger will evaluate the data collected and represent the current state of the system. Trigger contains two statuses, "OK" and "PROBLEM", to determine the threshold for what is "acceptable" data. Therefore, if the incoming data exceeds an acceptable state, the trigger status changes to "PROBLEM", the trigger status is recalculated every time the Zabbix server receives a new value. Zabbix server will send trigger status to electronic mail (e-mail) and Telegram application as notification for network administrators.